(untitled) (NTU Journal of Agriculture and Veterinary Science, 2021)
The principal objective of this experiment was to determine the type of bacterial associated with Ziziphus spina-christi (L.) tree showed individual colonies of Acinetobacter spp. and Molecularly diagnosed by using molecular diagnostic technology ( PCR) polymerase chain reaction by using some biochemical tests. It is the first recording of Acinetobacter Ziziphus spina-christi (L.) tree in Iraq.